What approach does the Austrian School of Economics and Christianity take on the role and rights of private property? - Rodrigues, Syer (2024)
This study aims to review the existing literature on the approach taken by the Austrian School of Economics and Christianity from the point of view of the origin, content, and motivation of these views on the function and rights of private property. This research is justified by the video produced by the Economic Forum with guidelines for the end of private property. The analysis categories defined for this research were: Social function of private property; Property rights; Private property as the basis for human prosperity; and Arguments against the abolition of private property. Considering the categories of analysis, the results point to the divergence between Christianity and the Austrian School regarding the origin of the researched themes. Regarding the content, the Christian and Austrian views are convergent. As for motivation, the two ideas converge on property rights and the arguments against private property abolition. Both views partially converge on private property and private property's social function as the basis for human prosperity. It is recommended to carry out works to deepen the theme, focusing on a possible influence of Reformed Theology in the Austrian School.